The Influence of Brand Image on Customer Buying Behavior at PT. Duta Maha Jaya Medan - Monang Tarigan; Sri Aprianti tarigan; Edward Harnjo; Javerson Simamora; Eddy Gunawan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Increased global competition, many organizations facing formidable challenges are increasingly using brand image as an important strategic management tool. Brand image allows producers to differentiate and position of products from that of competitors and assists consumers in the selection of an appropriate product. Brand image also included the customer responses to the brand name, sign or impression, and also represented the symbol of the product quality. A strong positive brand image is highly essential for corporations to compete effectively in today hyper competitive business environment. It enables corporations to gain competitive advantage by influencing consumer behavior and brand equity. PT. Maha Duta Jaya - Medan, which is engaged in sales of Yamaha motorcycles, must create a good brand image to face the market competition today. This to get greater sales revenue and having customer positive perception on company’s products. As motorcycle has become a fashion trend among young people in Indonesia and market begin to offer various kinds and types of motorcycles made the competition gets tougher. To face this competition problem, company need to build brand image for company’s product and company should to observe the customer buying behavior. Because customer buying behavior also changes with follow the offer which were given to. The research design used in this study is correlation research. The correlation research was designed by gathering necessary information as interviews and observations. Interviewing and observing company’s customers will allow for the most up to date, valid information possible. The method of research in here is descriptive method. The relationship between brand image and customer buying behavior at PT. Duta Mahajaya – Medan. According to analysis of correlation coefficient Product moment r= 0,79 Which means there is a Strong Positive Relationship between variable X and variable Y. It’s mean, brand image really influence to customer buying behavior. The results of this study indicate that there is a considerable influence of brand image on customer buying behavior. This can be seen from the relationship between the dimensions of brand image on customer purchase behavior, especially towards the model behavior.